Improvement on work measurement at Pau Mira Frozen Food Industry - Zulkifli, Muhammad Farez Najmi; Bong, Leo; Mohd Yaacob, Nur Syuhada; Yap, Alycia Ching Hui; San, Chin Whay; Mahmood, Salwa; Mohamed, Norirda (Penerbit UTHM, 2020)
The record of highest sales for one day is 20000 buns and the manpower for Pau Mira factory is only 18 persons. Special feature for Pau Mira is about the full of stuffing and many choices of flavor. Hot selling bun flavor is red bean bun and chocolate bun. For example, Bun Mira contains many flavors such as red bean bun, coconut, yam, chocolate, chicken, durian and it is enables to be food supplies to West Malaysia, not only limited to area Pagoh. The workflow for Pau Mira factory includes ingredient selection, dough kneading, and bun formation, fermentation, steaming, cooling and packaging. Table 5.1 shows the process of making pau started from dough kneading until the packaging process.